Nanomedicine-based adjuvant therapy: a promising solution for lung cancer - Yiming Xu; Jessica C. Hsu; Liyun Xu; Weiyu Chen; Weibo Cai; Kai Wang (Journal of Nanobiotechnology, 2023)
Abstract Lung cancer has been the leading cause of cancer-related deaths worldwide for decades. Despite the increasing understanding of the underlying disease mechanisms, the prognosis still remains poor for many patients. Novel adjuvant therapies have emerged as a promising treatment method to augment conventional methods and boost the therapeutic effects of primary therapies. Adjuvant therapy based on nanomedicine has gained considerable interest for supporting and enhancing traditional therapies, such as chemotherapy, immunotherapy, and radiotherapy, due to the tunable physicochemical features and ease of synthetic design of nanomaterials. In addition, nanomedicine can provide protective effects against other therapies by reducing adverse side effects through precise disease targeting. Therefore, nanomedicine-based adjuvant therapies have been extensively employed in a wide range of preclinical and clinical cancer treatments to overcome the drawbacks of conventional therapies. In this review, we mainly discuss the recent advances in adjuvant nanomedicine for lung cancer treatment and highlight their functions in improving the therapeutic outcome of other therapies, which may inspire new ideas for advanced lung cancer therapies and stimulate research efforts around this topic. Graphical Abstract